Фамильный оберег. Отражение звезды: роман / И. А. Мельникова - Мельникова Ирина (Ключи судьбы, 2012)
Экземпляры: (20190208) / Инвентарный номер: 30938 / Цена: / Авт.знак: М 48 / ГРНТИ: 17.82.31 / ББК: 84(2 РОС=Рус)6